2015
DOI: 10.1186/s12877-015-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Senior orienteering athletes as a model of healthy aging: a mixed-method approach

Abstract: BackgroundThe proportion of individuals reaching an old age is increasing and will, in the near future consume a majority of health care resources. It is therefore essential to facilitate the maintenance of optimal functionality among older adults. By characterizing older individuals experiencing wellbeing, factors important to promote and maintain health through life can be identified. Orienteering is an endurance-running sport involving cross-country navigation, demanding both cognitive and physical skills o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
16
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 28 publications
4
16
1
2
Order By: Relevance
“…The study population reported a mean GSRS score of 1.9 ± 0.8, suggesting that a large proportion of the study participants did experience no or mild gut complaints, results that are in line with our previous study [ 4 ]. Thus, the study population was also comprised of persons experiencing no gastrointestinal symptoms, without the possibility to experience an improvement during the intervention.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study population reported a mean GSRS score of 1.9 ± 0.8, suggesting that a large proportion of the study participants did experience no or mild gut complaints, results that are in line with our previous study [ 4 ]. Thus, the study population was also comprised of persons experiencing no gastrointestinal symptoms, without the possibility to experience an improvement during the intervention.…”
Section: Discussionsupporting
confidence: 90%
“…Acute and chronic diarrhea is frequently observed often resulting in an aberrant stool pattern restricting the older adults’ everyday life [ 1 , 2 ]. A well functioning gastrointestinal tract is essential for older adults to experience life-satisfaction and meaningfulness [ 3 , 4 ]. Today, little is known about the mechanisms behind age-associated gut problems and few treatment options designed only for older adults exist.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of food and mealtime setting for older adults has been previously described [ 25 , 26 ]. Furthermore, experiencing gut health was discussed as an important factor for optimal functionality, however, in contrast to previous research from our group this was not discussed by the SA [ 27 ].…”
Section: Discussioncontrasting
confidence: 58%
“…Nearly 50% of elderly above the age of 55 year’s experience GI symptoms 3 , 4 and in nursing homes, the prevalence increases to 70% 5 . Life satisfaction is strongly linked to a well-functioning GI tract 6 , 7 and diseases of the digestive system are known to lead to a higher symptom burden affecting the overall health status negatively in the elderly 8 . Previous studies have reported a stronger level of anxiety and depression in elderly with GI symptoms 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%